An Empirical Investigation of Service Quality, Usage and Mobile Banking in Predicting Adaptive Performance: Serial Mediation Model - HUSSAIN, ABID; ALI, DR. MAJID; AHMAD, DR. NISAR; KHAN, DR. MUBBSHER MUNAWAR; DANISH, DR. RIZWAN QAISER (The journal of contemporary issues in business and government, 2021)
This study investigates the serial mediation between Service quality and adaptive performance of managers through usage and mobile banking in contextual framework of SMEs’ enterprises of Pakistan. This study aims to find out how usage and mobile banking sequentially mediate the relationship between Service quality and adaptive performance of managers at the workplace. This study’s target population includes managers or owners of SMEs listed in Chambers of Commerce of Capital cities of Pakistan. As part of the more extensive research, 422 responses were received, which shows a 50% response. To test the hypotheses, structural and measurement models were developed in SEM. The findings show that serial mediation is observed in the case of service quality and adaptive performance as when we measure direct relation in the absence of mediators, it is significant and positive, as well as in the presence of serial mediators (usage and mobile banking) service quality, and adaptive performance is positive and significant. This study’s findings will help the academia, banking sector, SMEDA and practitioners understand the importance of service quality, usage of mobile devices and mobile banking on adaptive performance. Future researchers must focus on practical investigation of testing the effect of system quality, information quality and usage of mobile devices, mobile banking to predict managers’ adaptive performance by comparing SMEs and large enterprises in Pakistan.